Peranan Komitmen Sebagai Pengantara Dalam Mengukur Kesan Sikap Pekerja Terhadap Prestasi Kerja - Khatijah Othman; Siti Nurbaya Ismail; Shahrul Hafifi Mohd Fuad; Masni Md Hasim; Fadilah Othman; Muhammad Rahmat Abdullah; Norwini Zaidi; Nur Adlina Addenan; Nik Nadian Nisa Nik Nazli (Academic Inspired Network, 2024)
Workers attitudes are the main factor in determining job performance of each worker have achieved the requirement standard set by the organization. Should the worker have hi gh commitment towards their job, it is believed that it can lead to the development good character and indirectly enhance work performance. Moreover, workers with good attitudes in work places will affect the level of commitment and positive job performanc e that will be an added value to the organization. Hence, this study purpose is to examine whether worker commitment can be a moderating factor in measuring workers attitude towards job performance in an organization. The study respondent consists of profe ssional level officer and administrative personnel in organization. The research employed quantitative method. A set of questionnaire has been distributed to 99 respondent online. Research data was analyzed using Structural Equation Modelling (SEM) using A MOS software version 23. Finding gathered indicate that worker commitment is a moderating factor between workers attitude and job performance. It is further reported that worker in organization practise good attitude by showing high level of commitment (64 %) and thus it influence job performance up to 84%. In this particular study it is clear that worker commitment does help in enhancing job performance should the workers practising good attitude and virtuous character. This will contribute to effective out come and better productivity in achieving organizational objectives as a whole